Tangible figurine story composer and narrator - Choo, Jin He (Nanyang Technological University, 2023)
Tangible User Interfaces (TUIs) hold promise for enhancing learning, particularly among children, including those with Autism Spectrum Conditions (ASC). This report addresses challenges in ASC-focused TUIs, including cost and standardization issues. It reviews two ASC TUI projects, highlighting innovations and limitations.